Academic E-Books Publishers, Librarians, and Users - Ward, Suzanne M. (Charleston Insights in Library, Archival, and Information Sciences, 2015)
Academic E-Books: Publishers, Librarians, and Users provides readers with a view of the changing and emerging roles of electronic books in higher education. The three main sections contain contributions by experts in the publisher/vendor arena, as well as by librarians who report on both the challenges of offering and managing e-books and on the issues surrounding patron use of e-books. The case study section offers perspectives from seven different sizes and types of libraries whose librarians describe innovative and thought-provoking projects involving e-books.